Normobaric hypoxic conditioning in men with metabolic syndrome. Issue 24 (18th December 2018) - Klug, Lars; Mähler, Anja; Rakova, Natalia; Mai, Knut; Schulz‐Menger, Jeanette; Rahn, Gabriele; Busjahn, Andreas; Jordan, Jens; Boschmann, Michael; Luft, Friedrich C.
Abstract: The evidence that physical exercise lowers metabolic and cardiovascular risk is undisputed. Normobaric hypoxia training has been introduced to facilitate the effects of exercise. We tested the hypothesis that hypoxia training augments exercise‐related effects. We randomized 23 men with metabolic‐syndrome to single‐blinded exercise at normoxia (FiO2 21%) or hypoxia (FiO2 15%). Six weeks endurance training on a treadmill, 3 days per week, over 60 min at 60% V O2 max was required. The study included the following: (1) metabolic phenotyping by indirect calorimetry and adipose and muscle tissue microdialysis to gain insight into effects on resting, postprandial, and exercise metabolism, (2) cardiac imaging, and (3) biopsies. Primary endpoint was the change in cardiorespiratory fitness; secondary endpoints were as follows: changes in body weight, waist circumference, blood pressure, cardiac dimensions, and adipose and muscle tissue metabolism and gene expression. Our subjects reduced waist circumference and improved several cardiovascular risk markers including blood pressure. However, these effects were similar in both training groups. Cardiac dimensions were not influenced. We focused on glucose metabolism. After an oral glucose load, adipose tissue metabolism was significantly shifted to a more lipolytic state under hypoxia, whereas muscle metabolism was similar under both conditions. Postprandial energy expenditure was significantly increased under hypoxia, whereas activity energy expenditure was improved under normoxia. Gene expression was not consistently influenced by FiO2 . Adipose tissue triglyceride lipase, leptin, and hypoxia‐inducible factor‐alpha expression were increased by normoxia but not hypoxia. Abstract : We had reported earlier that altitude (normobaric hypoxia) training at FIO2 15% might facilitate the effects of exercise training in normal people. We now tested this hypothesis in men with the metabolic syndrome. Exercise lowered blood pressure, reduced waist circumference, and improved metabolism. Adding hypoxia during training, however, caused no further improvement.